Optimization of the optical array geometry for IceCube-Gen2 - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
IceCube-Gen2 is a planned extension of the IceCube Neutrino Observatory at the South Pole designed to study the high-energy neutrino sky from TeV to EeV energies with a five times better point source sensitivity than the current IceCube detector. This is achieved by deploying 120 new strings with attached optical sensors in a pattern around IceCube that features considerably larger distances between individual strings than the ∼125 m for the existing detector. Here, we present the results of an optimization study searching for the best point source sensitivity while varying the IceCube-Gen2 string spacing between 150 m and 350 m.
CRIS-Team Scopus Importer:2023-08-15